Pegaptanib: choroidal neovascularization in patients with age-related macular degeneration and previous arterial thromboembolic events. Issue 1 (January 2018) - Battaglia Parodi, Maurizio; Di Bartolo, Emanuele; Brue, Claudia; Cappello, Ezio; Furino, Claudio; Giuffrida, Sebastiano; Imparato, Manuela; Reibaldi, Michele
Purpose: To evaluate the efficacy and the rate of side effects of the pegylated aptamer pegaptanib in the treatment of patients with choroidal neovascularization (CNV) secondary to age-related macular degeneration (AMD) and a history of previous arterial thromboembolic events (ATEs). Methods: Twenty-three eyes of 23 patients with subfoveal CNV due to AMD and cerebrovascular accidents (n = 12) and myocardial infarction (n = 11) in the previous 6 months received intravitreal pegaptanib 0.3 mg according to a pro re nata regimen and were followed for 12 months. The paired Student t test was used to evaluate mean changes in best-corrected visual acuity (BCVA; primary outcome measure) and central foveal thickness (CFT). Results: The mean patient age was 71.5 ± 4.6 years; there were 14 women and 9 men. The CNV was type 1, 2, and 3 in 18, 3, and 2 eyes, respectively. The mean BCVA improved from 0.67 ± 0.23 logMAR at baseline to 0.52 ± 0.31 logMAR at the end of 12-month follow-up (p = 0.044). Thirty-five percent of patients achieved ≥3 Early Treatment Diabetic Retinopathy Study lines improvement at 12 months. Mean CFT at baseline (381 ± 111 µm) decreased to 304 ± 82 µm at 12 months (p = 0.008). Patients received a mean of 4.3 ± 1.3 (range 3-7) injections. No systemic or ocular side effects occurred; no patient experienced further ATEs. Conclusions: Intravitreal pegaptanib can be considered a viable treatment option for patients with AMD-related CNV who are at high risk of ATEs.